GAMBARAN PENGETAHUAN DAN SIKAP REMAJA PEROKOK TENTANG KESEHATAN GIGI DAN MULUT DI DESA CIBEBER KABUPATEN LEBAK BANTEN (Jurnal Kesehatan Siliwangi, 2021)
There are some problems with the impact of smoking on dental and oral health, and many ignore it. Public knowledge about tobacco and the dangers of smoking is minimal, especially in the lower middle class. This research is descriptive research with the survey of questionnaire questions in the form of google form, so that an overview of the knowledge and attitudes of adolescent smokers about dental and oral health in Lebak Banten. The subjects of the study were 30 adolescent respondents who were given questionnaires in the form of google forms. The results of this study showed that good knowledge as much (13.3%), the category is quite good as much (43.3%), the category is not good as much (43.3%) and good attitude as much (6.6%), quite good as much (23.3%), less good as much (70%). From the results of the study, it is known that the level of knowledge and attitude of adolescent smokers about dental and oral health in Lebak Banten 2021 is not good category.